Quantum Kinetics of the Electronic Energy Transformation in Molecular Nanostructures - Kucherenko, M.G.; Chmereva, T.M. (My University, 2023)
A quantum theory of electronic energy transfer in a layered nanostructure with molecular J-aggregates of polymethine dyes was proposed. An expression for the exciton-plasmon bond energy depending on various parameters of the system was given. The rate of non-radiative Fὄrster resonance energy transfer (FRET) from surface plasmon polaritons (SPPs) of a metal substrate to Frenkel excitons of J-aggregates was determined and dispersion dependences for hybrid states were obtained. It was established that the energy transfer rate can reach values of 1012–1013 s–1, and the value of the Rabi splitting is up to 100 MeV. The kinetics of the process under strong exciton-plasmon interaction was investigated. The time dependence of the energy exchange between the system components had the form of damped oscillations depending on the relaxation parameters, the Rabi frequency, and the response to resonance. In addition, the exciton FRET between two parallel monolayers of J-aggregates of polymethine dyes separated by a nanometer-thick metal film was investigated. It was found that the presence of the metal layer increases the FRET rate. The spin evolution of a pair of two triplet (T) molecules localized in the nano-cell region under the over-barrier jumps regime in a magnetic field was studied. The influence of the parameters of the two-dimensional potential on the frequency of inter-dimensional motions and the population of triplets was considered. The spin dynamics of molecular T-T pairs in the magnetic field of a ferromagnetic globular nanoparticle under free surface diffusion of a spincarrying molecule was investigated.
Keywords: non-radiative energy transfer; surface plasmon; J-aggregate; Frenkel exciton; triplet-triplet annihilation; dispersion curves; spin dynamics; globular nanoparticle; Rabi splitting